1980
DOI: 10.1037/0003-066x.35.5.409
|View full text |Cite
|
Sign up to set email alerts
|

On the permanence of stored information in the human brain.

Abstract: Many people believe that information that is stored in long-term memory is permanent, citing examples of "retrieval techniques" that are alleged to uncover previously forgotten information. Such techniques include hypnosis, psychoanalytic procedures, methods for eliciting spontaneous and other conscious recoveries, and-perhaps most important-the electrical stimulation of the brain reported by Wilder Penfield and his associates. In this article we first evaluate • the evidence and conclude that, contrary to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
280
2
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(288 citation statements)
references
References 14 publications
(24 reference statements)
3
280
2
3
Order By: Relevance
“…All statistical analyses were performed in two-tailed fashion with an α-level of 0.05, and the dependent variable was hit rate minus false alarm rate unless noted otherwise. Much research effort has been devoted to uncovering whether existing declarative memories can be erased by learning new materials (without the reactivation component), and the results have been underwhelming (30). Consistent with these findings, results in experiment 1 (n = 146) showed that relearning produced no impairment of the original memory in the absence of reactivation (t = 0.002; Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…All statistical analyses were performed in two-tailed fashion with an α-level of 0.05, and the dependent variable was hit rate minus false alarm rate unless noted otherwise. Much research effort has been devoted to uncovering whether existing declarative memories can be erased by learning new materials (without the reactivation component), and the results have been underwhelming (30). Consistent with these findings, results in experiment 1 (n = 146) showed that relearning produced no impairment of the original memory in the absence of reactivation (t = 0.002; Fig.…”
Section: Resultssupporting
confidence: 76%
“…Decades of behavioral research in humans has revealed that it is easy to alter people's memory reports and to create false memories (40), but the question surrounding whether it is possible to experimentally erase existing memories in humans has been far more contentious (30). Here, we demonstrate that retrieval can destabilize a declarative memory and render it susceptible to an amnesic treatment by relearning even after a substantial delay (i.e., at least 48 h).…”
Section: Discussionmentioning
confidence: 89%
“…Another related finding was that much more information is preserved in one's long term memory than one is aware of (for a discussion of this issue see Loftus, & Loftus, 1980). This was particularly obvious in case of mind-pops of English words which had been apparently learned previously but L.K.…”
Section: Discussionmentioning
confidence: 99%
“…For example the effect of misleading questions on witnesses raised the question of whether long term memories are stored permanently in the brain or can be alteted or replaced aftewards (Loftus & Loftus, 1980). Other theories were proffered to explain how misIeading questions affect a yimess' ability to gîve an accurate account of the events.…”
Section: Introductionmentioning
confidence: 99%